2018
DOI: 10.1111/echo.14132
|View full text |Cite
|
Sign up to set email alerts
|

Simplified apical four‐chamber view evaluation of relative apical sparing of longitudinal strain in diagnosing AL amyloid cardiomyopathy

Abstract: Simplified RAS LS evaluation represents an attractive approach for diagnostics of ALAC. However, because of considerable overlap with other disorders with hypertrophic phenotype, the analysis of RAS LS in the A4C should be combined with other traditional echocardiographic and ECG predictors in differentiating ALAC from other forms of concentric LV wall thickening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…However, increased relative apical strain (apical sparing) appears to be an accepted indicator for the presence of CAM—with reported values ranging from 0.97 ± 0.3 [ 24 , 25 ] to 2.0 ± 1.8 [ 26 ]. Relative apical strain in our patients with CAM confirmed the data of Phelan et al [ 26 ] and Fikrle et al [ 44 ]. However, by trend, a discrete increase of relative apical strain was also present in LV-NC (Tab.…”
Section: Discussionsupporting
confidence: 92%
“…However, increased relative apical strain (apical sparing) appears to be an accepted indicator for the presence of CAM—with reported values ranging from 0.97 ± 0.3 [ 24 , 25 ] to 2.0 ± 1.8 [ 26 ]. Relative apical strain in our patients with CAM confirmed the data of Phelan et al [ 26 ] and Fikrle et al [ 44 ]. However, by trend, a discrete increase of relative apical strain was also present in LV-NC (Tab.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the specificity of this technique is limited. Studies based on ECG and MRI found a characteristic apical-sparing pattern in patients with AL-CA (33,34), in which the apical longitudinal strain was relatively normal, whereas the basal and middle strains were reduced, suggesting that amyloid deposition in the apical region is less than that in the basal region. Therefore, the resistance to deformation may be lower (35).…”
Section: Discussionmentioning
confidence: 99%